Recalibrating Intimacy: Temporalities of the Rural in Elyse Bouvier’s Chinese Restaurant Photographs (Imaginations: Journal of Cross-Cultural Image Studies, 2016)
Abstract | In her documentary photographs of Chinese restaurants in small-town Alberta, Elyse Bouvier recalibrates intimacy. Her photographs wrench the intimate out of the sphere of the domestic and the private and insert it into the realm of the communal and the public. They offer us a vision of the kind of intense relation that can exist between strangers—stranger intimacy. Moreover, the images assert a temporality that is necessary for this recalibration. Intimacy does not exist outside of time. These photographs insist upon, and demand, an understanding of intimacy that is not only strange, but also deeply structured by a complex temporality—a kind of uncanny double take or déjà vu. Bouvier’s photographs demand that the viewer pause and dwell in the déjà vu that they produce.Résumé | Dans son documentaire photographique sur les restaurants chinois des petites villes rurales albertaines, Elyse Bouvier réévalue l’intime. Ses images arrachent l’intime de la sphère domestique et privée et l’intègre à l’espace communautaire et publique. Ces images nous offrent une vision du genre de relation intense qui peut exister entre inconnus- intimité étrange. De plus, les images affirment une temporalité nécessaire à cette réévaluation. L’intime n’existe pas en-dehors du temps. Ces images demandent et insistent sur une certaine compréhension de l’intime qui est non seulement étrange mais aussi profondément construit par une temporalité complexe ; une sorte de temps d’arrêt troublant ou de déjà-vu. Les images de Bouvier exigent que le spectateur s’arrête et s’attarde sur le sentiment de déjà-vu produit.